Pengaruh Biochar, Kompos dan Pupuk Hayati Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah Varietas Bima Brebes - Cicik Oktasari Handayani; Triyani Dewi; Anik Hidayah (Jurnal Hortikultura Indonesia (JHI), 2021)
The planting of shallots in the rainy season in dry land and highlands usually face pests and diseases problem. The purpose of this study was to determine the effect of biochar, compost and biological fertilizers on the growth and yield of the Bima Brebes variety of shallots that were cultivated in the highlands. Compositional materials used for compost include manure, sugar cane cake, bran, lime, molasses, EM4 and water. The biochar is made from corn cobs and the biological fertilizer used is a biological fertilizer that has been traded under the trademark Actino. This research was conducted in Igirklanceng Village, Sirampog District, Brebes Regency. The experiment used a Randomized Block Design (RAK) with 3 replications. The treatments given were consisted of the ameliorant types, including of 8 treatment, namely control (T0), compost (T1), biochar (T2), biochar+compost (T3), biological fertilizer (T4), biochar+biological fertilizer (T5), compost+biological fertilizer (T6), biochar+compost+biological fertilizer (T7), farmer treatment (T8). The results of this study indicate that the application of compost, biochar and biological fertilizer (T7) can increase the growth of shallot plant , especially in the number of leaves by 19.05% compared to the control. The shallot wet weight and dry weight of tubers per plot were 36.60% and 25.14% higher than the control treatment. The results revealed that Bima Brebes shallot variety is not suitable for planting in the highlands because it produces the small tubers.